Quality of Life and Adjustment to Psychosocial Morbidity Among Adults Attending a Dermatology Clinic - Oke OO (Annals of Health Research, 2021)
Background: The skin is the largest organ in the body and has aesthetic significance. The presence of any skin lesion or skin disease might be associated with psychosocial morbidity and negative impact on the quality of life.